Sensitivity and specificity of different measures of adiposity to distinguish between low/high motor coordination - Lopes, Luís (2015)
This study aimed to determine the ability of different measures of adiposity to discriminate between low/high motor coordination and to evaluate the relationship between different measures of adiposity and motor coordination. METHODS: This study included 596 elementary school children aged 9 to 12 years (218 females - 47.1%). Weight, height, and waist circumference were objectively measured by standardized protocols. Body fat percentage was estimated by bioelectric impedance. Body mass index and waist-to-height ratio were computed. Motor coordination was assessed by the Korperkoordination Test fur Kinder. Cardiorespiratory fitness was predicted by a maximal multistage 20 m shuttle-run test of the Fitnessgram Test Battery. A questionnaire was used to assess the maternal educational level. RESULTS: The receiver operating characteristic performance of body fat percentage in females and waist circumference in males presented a slightly better discriminatory accuracy than body mass index, waist circumference and waist-to-height ratio in predicting low motor coordination. After adjustments, logistic regression analyses showed that body mass index (beta=2.155; 95%CI: 1.164-3.992; p=0.015 for girls; beta=3.255; 95% CI: 1.740-6.088; p<0.001 for males), waist circumference (beta=2.489; 95%CI:1.242-4.988; p=0.010 for girls; beta=3.296; 95%CI:1.784-6.090; p<0.001 for males), body fat percentage (beta=2.395; 95%CI:1.234-4.646; p=0.010 for girls; beta=2.603; 95%CI:1.462-4.634; p<0.001 for males) and waist-to-height ratio (beta=3.840; 95%CI:2.025-7.283; p<0.001 for males) were positively and significantly associated with motor coordination in both sexes, with the exception of waist-to-height ratio in girls (beta=1.343; 95%CI:0.713-2.528; p=0.381)